Differential expression of 16 genes coding for cell cycle – and apoptosis-related proteins in vitamin D-induced differentiation of HL-60 cells - Kanli, A.; Savli, H. (Experimental Oncology, 2007)
Objective: The aim of the study was to analyze expression of several genes related to cell cycle regulation and apoptosis in realization of 1alpha,25-dihydroxyvitamin D3 (1,25(OH)2D3)-induced differentiation of HL-60 cells. Methods: The cultured HL-60 cells were treated with 1,25(OH)2D3. Quantitative real-time PCR was used for analyzing the changes in expression of 16 genes (Bcl-2, Bcl-xL, Mcl-1, Bik, caspase 6, caspase 7, cytochrome c, TNFR1, Myc, TGF-beta, JNK1, p38MAPK, p21, p27, Cdk2, cyclin E) at early phases of cell differentiation of HL-60 cells induced by 1,25(OH)2D3. Results: Among investigated genes, Bik and Myc gene expression was down-regulated at 48 h time points. JNK1 gene was markedly up-regulated and caspase-6 and cyclin E genes were down-regulated at 18 h time point. Conclusion: These findings suggest that there are no distinct apoptotic signals at early phases of cell differentiation. It is speculated that changes in the expression of the genes involved in vitamin D-induced apoptosis of HL-60 cells could be better visualized after the terminal stages of cell differentiation. Цель: проанализировать экспрессию ряда генов, участвующих в регуляции клеточного цикла и апоптоза в дифференцировке клеток
HL-60 промиелоцитарного лейкоза человека, индуцированной 1альфа,25-дигидроксивитамином 3(1,25(OH 2 3). Методы:
культивируемые клетки HL-60 инкуировали с 1,25(OH 2
D3. Количественную ПЦР в режиме реального времени использовали для анализа изменений экспрессии 16 генов (Bcl-2, Bc l-xL , l 1, k, каспаза 6, каспаза 7, цитохром с, TNFR1, Myc, TGF- beta, K 1,
p38 MAPK, p21, p , Cdk2, иклин Е ) при индукции апоптоза и дифференцировки в клетках HL-60 под дествием 1,25(OH 2
D3. Результаты: среди исследованных генов отмечено снижение экспресси Bik и Myc через 48 ч. Экспрессия гена JNK1 повышена, а
генов каспазы-6 и циклина Е снижена в точке 18 ч. Выводы: эти данные свидетельствуют об отсутствии четких сигналов экспрессии
апоптоз-ассоциированных генов на ранних фазах клеточной дифференцировки. Предполагается, что изменения в экспрессии генов,
участвующих в реализации апоптоза клеток HL-60, индуцированного витаминомD, могут быть выражены лишь на терминальных
стадиях дифференцировки этих клеток.